La traduction pédagogique en didactique du fle - Sariyildiz, Aline (Vestnik za tuje jezike, 2025)
In the field of foreign language teaching and learning, pedagogical translation serves as a specific didactic tool, distinct from professional translation. Rather than aiming for perfect linguistic transposition for editorial or specialized purposes, pedagogical translation is part of an educational approach focused on developing learners’ linguistic, cultural, and cognitive skills. This article draws on the interpretive theory of transla-tion, which involves the stages of comprehension, deverbalization, reverbalization, and justificatory analysis, to propose a methodological approach for teaching French as a foreign language (FLE). The central hypothesis of this research is that the principles of the interpretive theory, as a model of interlinguistic mediation, can be adapted didactically to guide learners in producing progressive, contextualized, and formative translations. Through a series of activities, learners are encouraged to engage both their understanding of the source text and their ability to grasp meaning beyond words (deverbalization); they also develop linguistic creativity in reformulating the message in the target language. The reflective analysis of translation choices at the end of the process further promotes linguistic awareness and the development of metacognitive strategies. Thus, the article shows that translation, when viewed as a form of mediation, can become a tool to enhance FLE learning and support the development of learners’ written comprehension and production skills.
Keywords: didactique des langues; FLE; francoščina; French; interpretativna teorija prevajanja; interpretive theory of translation; language teaching; pedagogical translation; pedagoško prevajanje; poučevanje jezika; théorie interprétative; traduction pédagogique